Islam As Malay Identity: A Historical Perspective with A Special Reference to Lingga-Riau Sultanate - Anwar, Syamsul (Universitas Ahmad Dahlan, 2025)
This paper explores Islam as the foundational and enduring element in the formation of Malay cultural identity, with special reference to the Lingga-Riau Sultanate. Employing a historical and interpretive approach, it examines how Islam became deeply intertwined with the political, intellectual, and socio-cultural fabric of the Malay world. The discussion begins with a historical overview of the Lingga-Riau Sultanate (its genealogy, political evolution, and encounters with colonial powers) to contextualize the transformation of Malay society under Islamic influence. The study reveals that Islam not only served as a religious orientation but also as the moral, legal, and philosophical foundation of Malay civilization. It shaped the Malay worldview, governance, and expressions of culture, from court traditions and literary production to everyday ethical conduct. Within the Lingga-Riau Sultanate, Islam played a pivotal role in defining authority, social cohesion, and collective identity. The sultans and the Malay nobility were instrumental in cultivating Islamic literacy, promoting religious scholarship, and integrating Islamic values into governance. Even amid colonial suppression and political fragmentation, Islam continued to function as a unifying and resilient cultural force. The findings suggest that Malay identity, as manifested in Lingga-Riau, cannot be understood apart from Islam, which has long served as its defining marker and cohesive principle, a legacy that continues to inform the consciousness of the Malay world today.